Клиповость мышления и реализация принципа ситуативности в процессе обучения польских учащихся межкультурному общению на русском языке - Makarowska, Olga (Studia Rossica Posnaniensia, 2014)
The article deals with issues of using situational rules in teaching the Russian language to Polish students with regard to their personality traits that have been conditioned by the clip type of thinking. The article also discusses the influence that clip thinking has on students’ emotional sphere and its reflection in Russian language acquisition. The article presents certain proposals for including emotive factors in communicative situations and for coordinating situational and communication exercises during Russian language classes.